The influence analysis of Service and Price Perceptions on Customer Satisfaction of the Umrah Pilgrims of PT Cahaya Haramain Semarang - Eka Ratri Yuniastuti; Noor - Suroija; Irawan - Malebra (Politeknik Negeri Semarang, 2020)
The research aims to determine whether service and price perception had a significant influence on customer satisfaction in PT Cahaya Haranain Semarang. The data collection method were done by using a questionnaire. The measurement scale in the questionnaire of this research is the Agree Disagree Scale with a scale of 10. The amount of the questionnaires that had been completed were 70 units. The data analysis was conducted by using SPSS version 24, which produces the equation, namely Y = 3,323 + 0,360X1 + 0,257X2. This equation has a regression value of the service variable which most dominantly influence customer satisfaction of 0,360, followed by the price perceptions variable with a regression value of 0,257. If the independent variable is 0, then there was other variable that influence customer satisfaction by 3,323. It explains the determining factors of customer satisfaction, namely service and price perception that have a significant influence on the customer satisfaction of the umrah pilgrims. There are some limitations. The first, the research object is the umrah pilgrims in PT Cahaya Haramain. It is not generalized to other umrah travel. The second, this study only contains two main variables from the customer satisfaction, namely service and price perception